2021
DOI: 10.32718/nvlvet10402
|View full text |Cite
|
Sign up to set email alerts
|

System of antioxidant protection of the body of piglets under the action of feed additive “Sylimevit”

Abstract: One of the conditions for obtaining high-quality pig products is the use of feed additives, which contain all the necessary biologically active substances, eliminating their deficiency in feed and acting as catalysts for metabolic processes in pigs. That is why the aim of the study was to study the effect of feed additive “Sylimevit” on the enzymatic and non-enzymatic parts of the antioxidant system of piglets after weaning. Two groups of piglets were formed – control and experimental, in the amount of 10 indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
(12 reference statements)
0
3
0
5
Order By: Relevance
“…The obtained results indicate the inhibition of erythrocytopоesis with a simultaneous increase in the size of erythrocytes (macrocytosis) and their hemoglobin content due to digestive tract digestion and vitamin B12 absorption from the intestine. The established RDW norm of heterogeneity of red blood cells allowed minor deviations (7.9 %), which could be due to the redistribution of white blood cells, since according to Vyslotska et al (2021), in the period of stress, neutrophilia and eosinopenia are observed. However, the obtained RDW erythrocyte's anisotropy coefficient affected the ability to transport oxygen and carbon dioxide.…”
Section: Tablementioning
confidence: 99%
“…The obtained results indicate the inhibition of erythrocytopоesis with a simultaneous increase in the size of erythrocytes (macrocytosis) and their hemoglobin content due to digestive tract digestion and vitamin B12 absorption from the intestine. The established RDW norm of heterogeneity of red blood cells allowed minor deviations (7.9 %), which could be due to the redistribution of white blood cells, since according to Vyslotska et al (2021), in the period of stress, neutrophilia and eosinopenia are observed. However, the obtained RDW erythrocyte's anisotropy coefficient affected the ability to transport oxygen and carbon dioxide.…”
Section: Tablementioning
confidence: 99%
“…Важливу роль в підтримці прооксидантноантиоксидантного потенціалу відіграє еритроцитарний гомеостаз, що, крім того, забезпечує функціонування системи метаболізму Оксигену Martyshuk et al, 2021;Vyslotska et al, 2021). Знижена кількість еритроцитів у крові кнурів дослідної групи головним чином позначалася на їхніх антирадикальних й антигіпоксичних здатностях (рис.…”
Section: рис 2 основні показники гоместазу кнурівunclassified
“…Дослідження багатьох як вітчизняних, так і закордонних науковців спрямовані на стимулювання природних захисних властивостей організму тварин (Krempa & Kozenko, 2018;Martyshuk et al, 2020;Taşlıdere et al, 2022;Saifi et al, 2022;Askin et al, 2022), здатних зменшити негативний вплив технологічного процесу та зміцнювати імунні функції організму. Значне зацікавлення дослідники виявляють до застосування імуностимуляторів різного походження, до яких належать не лише фармакологічні форми, а й біологічно активні кормові добавки, пробіотики (Kovalenko & Yamtsul, 2012;Vyslotska et al, 2021;Kozenko et al, 2021).…”
Section: вступunclassified